2015
DOI: 10.6061/clinics/2015(05)01
|View full text |Cite
|
Sign up to set email alerts
|

Serum interleukin-17 levels are associated with nephritis in childhood-onset systemic lupus erythematosus

Abstract: OBJECTIVES:To determine the serum interleukin-17 (IL-17) levels in childhood-onset systemic lupus erythematosus patients and to evaluate the association between IL-17 and clinical manifestations, disease activity, laboratory findings and treatment.METHODS:We included 67 consecutive childhood-onset systemic lupus erythematosus patients [61 women; median age 18 years (range 11-31)], 55 first-degree relatives [50 women; median age 40 years (range 29-52)] and 47 age- and sex-matched healthy controls [42 women; med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 38 publications
1
7
0
2
Order By: Relevance
“…Accordingly, patients with ANCA-associated vasculitis presented elevated serum levels of IL-17A and other Th17-related cytokines, such as IL-23 [ 89 ], whereas in ANCA-associated crescentic glomerulonephritis patients, only serum IL-17C but not IL-17A, F, or E levels were increased [ 90 ]. In addition, high serum and urine IL-17A levels were found in patients with systemic lupus erythematosus [ 91 , 92 ] and in other immune glomerulonephritis [ 93 , 94 ]. More recently, preclinical and clinical studies have shown the involvement of IL-17A in nonimmune nephropathies, including hypertensive [ 61 , 95 ] and diabetic nephropathy [ 96 , 97 ].…”
Section: Il-17a: a Key Proinflammatory Cytokine And Therapeutic Tamentioning
confidence: 99%
“…Accordingly, patients with ANCA-associated vasculitis presented elevated serum levels of IL-17A and other Th17-related cytokines, such as IL-23 [ 89 ], whereas in ANCA-associated crescentic glomerulonephritis patients, only serum IL-17C but not IL-17A, F, or E levels were increased [ 90 ]. In addition, high serum and urine IL-17A levels were found in patients with systemic lupus erythematosus [ 91 , 92 ] and in other immune glomerulonephritis [ 93 , 94 ]. More recently, preclinical and clinical studies have shown the involvement of IL-17A in nonimmune nephropathies, including hypertensive [ 61 , 95 ] and diabetic nephropathy [ 96 , 97 ].…”
Section: Il-17a: a Key Proinflammatory Cytokine And Therapeutic Tamentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE) is a chronic systematic autoimmune disease with high heterogeneity (1,2). SLE is more prevalent in women of reproductive age than in men (3)(4)(5). Although the etiology and pathogenesis of SLE have not been fully elucidated, the breakdown of immune tolerance induced by environmental stimulation and genetic factors is widely reported to play a core role in SLE (1,2,6,7).…”
Section: ' Introductionmentioning
confidence: 99%
“…Возможно, изучение растворимых форм sPD-L1 / PD-1 позволит преодолеть опухолевую гетерогенность и идентифицировать наиболее значимые предикторные и прогностические биомаркеры. Интерес представляет изучение концентрации интерлейкина-17А (interleukin-17А, IL-17А) в сыворотке крови, повышение которой отмечено у больных с аутоиммунными заболеваниями, в том числе и нефритами [13,14], а также трансформирующего фактора роста бета 1 (transforming growth factor beta 1, TGF-β1), являющегося основным иммуносупрессором.…”
Section: Introductionunclassified